A programming framework for distributed computing continuum systems - Zhao, Zhehao; Chen, Yifeng (Science of computer programming, 2026)
Distributed Computing Continuum Systems (DCCS) integrate a large-scale cloud side and a wide-area heterogeneous edge side within the same network environment and is therefore a more general computing paradigm than cloud or edge computing. There are currently no programming technologies suitable for the support of DCCS application development. In this paper, we introduce a programming framework called Wolfs, which uses only basic programming constructs from programming-language theories. The framework is communication-centric in the sense that high-level communication models and lower-level communication protocols are organised in a hierarchy. Data-processing computations are inserted in the hierarchy as actions. This design allows application-level information to influence network routing and connection management. Wolfs programming is demonstrated in two case studies.